Prognostic laboratory markers of joint damage in rheumatoid arthritis. Issue 2 (30th September 2004) - Lindqvist, E; Eberhardt, K; Bendtzen, K; Heinegård, D; Saxne, T
Abstract : Objective: To investigate whether determination of a set of laboratory markers at baseline provides prognostic information on joint damage in hands and feet in rheumatoid arthritis. Methods: 183 patients with early rheumatoid arthritis included in a prospective study were examined. Radiographic changes in hands and feet at 5 and 10 years after inclusion were evaluated (Larsen). The markers analysed were: erythrocyte sedimentation rate (ESR); HLA-DRB alleles typed by restriction fragment length polymorphism; and C reactive protein, cartilage oligomeric matrix protein (COMP), rheumatoid factor (RF) (IgG, IgA, and IgM subtypes), antibodies against cyclic citrullinated peptide (anti-CCP), and antibodies against interleukin 1α (anti-IL1α), analysed by immunoassays. Multiple linear regression with backward elimination was used to determine the prognostic value of the variables. Results: 117/176 patients were positive for IgG RF, 138/176 for IgA RF, 139/176 for IgM RF, 140/176 for anti-CCP, and 40/182 for anti-IL1α. After five years, ESR, the presence of IgA RF, serum COMP, and the presence of anti-CCP were significantly associated with more severe joint damage, and the presence of anti-IL1α with less severe joint damage. Baseline C reactive protein and anti-CCP predicted radiographic outcome after 10 years. A stronger prediction was obtained by combining the prognostic factors. Conclusions: Early determination of anti-CCP, IgA RF, anti-IL-1α, ESR, C reactive protein, and COMP predicted the development of joint damage in hands and feet in this cohort. A combination of these measures reflecting different aspects of the disease process should be useful for evaluating prognosis in individual patients with early rheumatoid arthritis.